2020
DOI: 10.21873/invivo.12077
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Analyses in Patients With Advanced Solid Tumors Treated With the LAT1 Inhibitor JPH203

Abstract: Background/Aim: Amino acids are among the most important nutrients for supplying energy and building protein blocks in cancers. L-type amino acid transporter (LAT) 1 is known to play a critical role in cancer growth. We have completed the first-inhuman phase I study using the LAT1-specific inhibitor JPH203. Patients and Methods: We evaluated plasma free amino acids (PFAAs), body mass index (BMI), and efficacy of JPH203 in patients enrolled in the phase I study. Results: LAT1-substrate PFAAs and branched chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The study indicated that the safety and efficacy of JPH203 could be predicted by genetic variants in the NAT2 gene, which encodes an N -acetyltransferase responsible for phase II metabolism of JPH203. The study also suggested that plasma free amino acid levels and BMI are useful predictors of JPH203 efficacy ( 136 ). Randomized controlled phase II studies in patients with advanced biliary tract cancer are under way in Japan (University Hospital Medical Information Network [UMIN] Clinical Trials Registry UMIN000034080).…”
Section: Metabolic Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…The study indicated that the safety and efficacy of JPH203 could be predicted by genetic variants in the NAT2 gene, which encodes an N -acetyltransferase responsible for phase II metabolism of JPH203. The study also suggested that plasma free amino acid levels and BMI are useful predictors of JPH203 efficacy ( 136 ). Randomized controlled phase II studies in patients with advanced biliary tract cancer are under way in Japan (University Hospital Medical Information Network [UMIN] Clinical Trials Registry UMIN000034080).…”
Section: Metabolic Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…This finding opens also other perspectives when considering that a therapy acting on CD98 trafficking will surely impair the LAT1 chaperoning, with consequent high relevance to human therapy. Then, CD98 inhibition would act synergistically with specific LAT1 inhibitors, such as the tyrosine derivative JPH203 that is in human trial for anticancer therapy 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, IGN523, a humanized anti-CD98 (anti-SLC3A2) monoclonal antibody has been tested for relapsed or refractory acute myeloid leukemia, and preclinical data showed effective anti-tumor activity in xenograft models ( 173 ). On the other hand, LAT-1 inhibitor JPH203 showed promising results in a phase I clinical trial for biliary tract cancer ( 174 ). Even though these modalities were designed to inhibit the amino acid uptake of tumor cells, such approaches might also target Treg functions to attenuate their immunosuppressive mechanisms, which might also favor the elimination of tumor cells.…”
Section: Tcf-1 and Tregsmentioning
confidence: 99%